Baptismal Font - Ghosh, Ayan (2023)
Adjacent to the west wall, on the left side of the entrance, is the baptismal font. The font was presented in 1861 and made from Caen stone. Five squat pillars made of green color Devonshire marble uphold the font. The squat pillars rest upon basements also made from Caen stone, which in turn is supported by a plinth made from basalt stone.